The Forgotten Irish? Contested sites and narratives of nation in Newfoundland - Trew, Johanne (Ethnologies, 2005)
The Irish in Newfoundland have developed their culture and identity over the past 300 years in the context of the island’s changing political status from independent territory, to British colony, and to Canadian province (since 1949). Newfoundland song, dance and dialect all display evident Irish features and have played an important role in the marketing of the province as a tourist destination. Recent provincial government initiatives to forge contacts with Celtic Tiger Ireland and thus revive this powerfully “imagined” Atlantic network have also contributed to the notion of the “Irishness” of Newfoundland culture. The narrative of Newfoundland as an Irish place, however, has always been (and continues to be) contested; this is most evident in a local discourse of space and place that is grounded in two predominant narratives of the Newfoundland nation: Republican and Confederate. The author illustrates how this contested spatial discourse has recently played out over the disputed terrain of the The Rooms, the new home of Newfoundland’s provincial museum, art gallery and archives.